Linkages between aggregate formation, porosity and soil chemical properties - Regelink, Inge C.; Stoof, Cathelijne R.; Rousseva, Svetla; Weng, Liping; Lair, Georg J.; Kram, Pavel; Nikolaidis, Nikolaos P.; Kercheva, Milena; Banwart, Steve; Comans, Rob N.J. (Geoderma, 2015)
Linkages between soil structure and physical–chemical soil properties are still poorly understood due to the wide size-range at which aggregation occurs and the variety of aggregation factors involved. To improve understanding of these processes, we collected data on aggregate fractions, soil porosity, texture and chemical soil properties of 127 soil samples from three European Critical Zone Observatories. First, we assessed mechanistic linkages between porosity and aggregates. There was no correlation between the fractions of dry-sieved aggregates (>1mm, DSA) and water-stable aggregates (>0.25μm, WSA). Soil microporosity and micro+mesoporosity increased with increasing abundance of aggregates, though this correlation was only significant for the WSA fraction. The fraction of DSA did not affect the overall porosity of the soil, but affected the ratio between micro- and mesopores (θ30kPa/θ0.25kPa), suggesting that micropores are dominantly located within DSA whereas mesopores are located in between DSA and loose particles. Second, we studied the relations between the physical and chemical soil properties and soil structure. Soil texture had only a minor effect on the fractions of WSA and DSA whereas Fe-(hydr)oxide content was correlated positively with both WSA fraction and porosity. This may be attributed to Fe-(hydr)oxides providing adsorption sites for organic substances on larger minerals, thereby enabling poorly reactive mineral particles to be taken up in the network of organic substances. The fraction of WSA increased with an increase in the soil organic carbon (SOC) and Fe-(hydr)oxides content and with a decrease in pH. This pH-effect can be explained by the enhanced coagulation of organically-coated particles at a lower pH. Overall, this study indicates that mechanistic linkages exist between soil chemical properties, aggregate formation and soil porosity. •We studied the linkages between aggregate formation, porosity and soil chemical properties.•The combination of texture and water-stable aggregates determines the porosity.•Dry-sieved aggregates control the distribution of pores between micro- and mesopores.•Fe-(hydr)oxides are important for the formation of pores and water-stable aggregates.•The combination of Fe-(hydr)oxides, soil organic matter and pH controls aggregate formation.